2009
DOI: 10.1039/b911257j
|View full text |Cite
|
Sign up to set email alerts
|

Water permeation through stratum corneum lipid bilayers from atomistic simulations

Abstract: Stratum corneum, the outermost layer of skin, consists of keratin filled rigid non-viable corneocyte cells surrounded by multilayers of lipids. The lipid layer is responsible for the barrier properties of the skin. We calculate the excess chemical potential and diffusivity of water as a function of depth in lipid bilayers with compositions representative of the stratum corneum using atomistic molecular dynamics simulations. The maximum in the excess free energy of water inside the lipid bilayers is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(134 citation statements)
references
References 42 publications
12
119
1
2
Order By: Relevance
“…Given the complexity of the composition of the skin lipids and the consensus over their molecular architecture, many researchers have developed skin-lipid 'substitutes' to explore the interaction of molecules within SC using MD simulation, which has a barrier function simi- lar to skin tissue [32]. Both single-component models [33][34][35][36] and mixed skin-lipid models with different compositions and contents [37][38][39][40] have been investigated. Das et al demonstrated that the simulated model bilayers comprising of CER2 (ceramide NS, the predominant ceramide in skin lipid with a C24:0 fatty acid tail, short for CER in the following passage), FFA (C24:0) and CHOL at ratio close to 2:2:1 has the most desirable properties of good barrier function and stability against mechanical stress [38,39].…”
Section: Bilayer Model Of Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the composition of the skin lipids and the consensus over their molecular architecture, many researchers have developed skin-lipid 'substitutes' to explore the interaction of molecules within SC using MD simulation, which has a barrier function simi- lar to skin tissue [32]. Both single-component models [33][34][35][36] and mixed skin-lipid models with different compositions and contents [37][38][39][40] have been investigated. Das et al demonstrated that the simulated model bilayers comprising of CER2 (ceramide NS, the predominant ceramide in skin lipid with a C24:0 fatty acid tail, short for CER in the following passage), FFA (C24:0) and CHOL at ratio close to 2:2:1 has the most desirable properties of good barrier function and stability against mechanical stress [38,39].…”
Section: Bilayer Model Of Scmentioning
confidence: 99%
“…Both single-component models [33][34][35][36] and mixed skin-lipid models with different compositions and contents [37][38][39][40] have been investigated. Das et al demonstrated that the simulated model bilayers comprising of CER2 (ceramide NS, the predominant ceramide in skin lipid with a C24:0 fatty acid tail, short for CER in the following passage), FFA (C24:0) and CHOL at ratio close to 2:2:1 has the most desirable properties of good barrier function and stability against mechanical stress [38,39]. Therefore, it can be used to investigate the interactions and elucidate the molecular mechanisms of the penetration enhancement effect of menthol.…”
Section: Bilayer Model Of Scmentioning
confidence: 99%
“…Studies of the gel to liquid-crystal phase transitions of fully hydrated bilayers were also performed 147,149,150 . It should be mentioned also a series of MD simulations of the specific branch-chained lipid bilayers [151][152][153][154][155] and a ceramide bilayer [156][157][158] .…”
Section: Bilayers: Lipids With Saturated Unsaturated and Polyunsatumentioning
confidence: 99%
“…Water permeability for a bilayer composed of a 2:2:1 molar ratio of ceramide NS 24:0 (ceramide 2) -CHOL -free FA 24:0 was estimated with extended ensemble MD in 158 .…”
Section: Small Moleculesmentioning
confidence: 99%
“…A series of simulations with a single water molecule constrained to remain at a fixed distance z from the midplane was used to calculate the local (in z) excess chemical potential and diffusivity of water inside SC lipid bilayers [26]. A large barrier for penetration (approx.…”
Section: S-chainmentioning
confidence: 99%